How do children’s hospitals address health inequalities: a grey literature scoping review - Rachel Isba; Liz Brewster; Pallavi Patel; Louise Brennan; Judith Lunn; Fiona Egboko; Dora Pestotnik Stres; Eleanor Broad (BMJ Open)
Objectives Health inequalities are systematic differences in health between people, which are avoidable and unfair. Globally, more political strategies are required to address health inequalities, which have increased since the global SARS-CoV-2/COVID-19 pandemic, with a disproportionate impact on children. This scoping review aimed to identify and collate information on how hospitals around the world that deliver care to children have addressed health inequalities.Design Scoping review focused solely on grey literature.Eligibility criteria for selecting studies Following Joanna Briggs Institute guidelines, a four-step approach to identifying literature was adopted.Data sources Overton, OpenGrey, OpenMD, Trip Database, DuckDuckGo, Google, targeted websites and children’s hospital websites were searched on March 2023 for items published since 2010.Data extraction and synthesis Retrieved items were screened against clear inclusion and exclusion criteria before data were extracted by two independent reviewers using a data extraction tool. Studies were tabulated by a hospital. A meta-analysis was not conducted due to the varied nature of studies and approaches.Results Our study identified 26 approaches to reduction of health inequalities, from 17 children’s hospitals. Approaches were categorised based on their size and scope. Seven approaches were defined as macro, including hospital-wide inequality strategies. Ten approaches were classed as meso, including the establishment of new departments and research centres. Micro approaches (n=9) included one-off projects or interventions offered to specific groups/services. Almost half of the reported approaches did not discuss the evaluation of impact.Conclusions Children’s hospitals provide a suitable location to conduct public health interventions. This scoping review provides examples of approaches on three scales delivered at hospitals across high-income countries. Hospitals with the most comprehensive and extensive range of approaches employ dedicated staff within the hospital and community. This review indicates the value of recruitment of both public health-trained staff and culturally similar staff to deliver community-based interventions.